Assessment of farm mechanization in the Philippines as basis for strategy formulation towards sustainable agriculture - Catanyag, Marianne Eleanor A. (University of the Philippines Diliman, 2011)
Geared towards the National Goal of Sustainable Agriculture, this paper aimed to assess the level of the Philippine agricultural mechanization and compare it to Asian countries such as China, Thailand, South Korea and Vietnam. Farm mechanization is verified to be one of the important agricultural inputs needed to increase farm productivity. In the Philippines, the level of farm mechanization is generally low and its development is very slow. The Philippines is also a net importer of farm mechanization technologies. Local manufacturers lack the technological capability and rely heavily on imported products for materials and some machine parts. Farmers' adoption of technology is also slow, regardless of the efforts exerted by several institutions to promote the utilization of farm machinery and equipment. Other Asian countries have evidently outperformed the Philippines in farm mechanization. China's mechanization almost doubled, from 3.8 hp/ha in 1990 to 6.6 hp/ha in 2010. South Korea leaped from 0.44 hp/ha to 4.1 hp/ha from 1960 to 1990, respectively, brought about by the Industrial Revolution. Thailand also exhibited immense improvement, from 0.8 hp/ha in 1990 to 4.4 hp/ha. Vietnam's farm mechanization was relatively low at 1.2 hp/ha but the Philippines was at the lowest ebb nailed at 0.5 hp/ha for almost two decades from 1990 to 2010. Issues that impede mechanization in the Philippines were identified as socio-cultural, technological, economic, and political factors. Recommendations from previous studies, objectives, agenda, programs, and initiatives to address these constraints are implemented in a fragmented, uncoordinated, and piecemeal manner which appears to be ineffective and inefficient. This study recommends selective farm mechanization as the overall strategy to improve the country's farm mechanization level. It also illustrates how the concepts and principles of technology management can be applied to come with a better game plan to ensure farmers' adoption of farm machinery which is primarily the success parameter of farm mechanization.